2020
DOI: 10.1161/circulationaha.120.045536
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Implantation Represents an Anti-Inflammatory Therapy Via Reduction of Shear Stress–Induced, Piezo-1–Mediated Monocyte Activation

Abstract: Background: Aortic valve stenosis is an increasingly prevalent degenerative and inflammatory disease. Transcatheter aortic valve implantation (TAVI) has revolutionized its treatment, thereby avoiding its life-threatening/disabling consequences. Whether aortic valve stenosis is accelerated by inflammation and whether it is itself a cause of inflammation are unclear. We hypothesized that the large shear forces exerted on circulating cells, particularly on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 50 publications
1
101
0
Order By: Relevance
“…The simplicity, controllability, versatility, and biocompatibility of the newly described technology make it highly suitable for multiple applications. These include important applications in physics (e.g., studying complex fluids and soft materials [5][6][7] and generation of droplets [58,59] ), chemistry (e.g., synthesis of various molecules and compounds [11,12] ), and biology (e.g., manipulation of cells, [60,61] performing multistep assays, [13] diagnostics, [62] and developing organ-on-a-chip platforms [63] for studying the mechanobiology of cells [64,65] and the human circulatory system [17,19,66] ). Notably, both customized harmonic and disturbed flow patterns can be created and studied using the newly described technology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The simplicity, controllability, versatility, and biocompatibility of the newly described technology make it highly suitable for multiple applications. These include important applications in physics (e.g., studying complex fluids and soft materials [5][6][7] and generation of droplets [58,59] ), chemistry (e.g., synthesis of various molecules and compounds [11,12] ), and biology (e.g., manipulation of cells, [60,61] performing multistep assays, [13] diagnostics, [62] and developing organ-on-a-chip platforms [63] for studying the mechanobiology of cells [64,65] and the human circulatory system [17,19,66] ). Notably, both customized harmonic and disturbed flow patterns can be created and studied using the newly described technology.…”
Section: Resultsmentioning
confidence: 99%
“…This includes studying mechanical and rheological properties of complex fluids and soft materials such as polymers, emulsions, colloids, liquid crystals, and their biological counterparts, [5][6][7][8][9][10] chemical synthesis of hazardous chemical compounds, pharmaceutical agents, and micro/nanomaterials, [11][12][13][14] and mimicking harmonic/disturbed flows occurring in the natural systems, such as the human circulatory system, where they may cause dysfunction or disease. [15][16][17][18][19] Passive and active mechanisms have been used to generate disturbed flow patterns in microfluidic systems. [20] The passive mechanisms take advantage of asymmetric geometries or sudden changes in the geometry to generate secondary flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it must be noted that while the focus of this study is the use of microscale EK techniques, microfluidic devices are currently being used across a wide range of fields. One such example, as presented by Baratchi et al [ 22 ], is the in vitro study of cell mechanobiology, including the effects of shear stress on cells. These developments in iEK techniques could be combined with other cell characterization systems, such as the one presented by Baratchi et al [ 22 ], which can result in a more comprehensive cell characterization process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that monocytes, which play an important role in coagulation, exhibit an activated phenotype in AS patients which reverses post-TAVI. 33 Although it is well accepted that platelets can be activated and desensitized by shear stress, there is a lack of data currently available regarding the effects of AS, and indeed TAVI, on platelet function. Therefore, mechanistic studies on the role of shear stress-induced effects on circulating blood cells will likely provide additional insights into the links between the potential prothrombotic effects and bleeding risk observed in patients undergoing TAVI.…”
mentioning
confidence: 99%